Restoration of degraded land for food security and poverty reduction in East Africa and The Sahel - World Agroforestry Centre (2020)
Land degradation threatens the livelihoods and the food and nutrition security of the poorest, most vulnerable smallholder farmers and pastoralists. As a result, migration is accelerating, with an estimated 60 million people in Sub-Saharan Africa at risk of being displaced by desertification and land degradation by 2050.